DESIGN OF A MILLIMETER WAVE E-PLANE WAVEGUIDE BANDPASS FILTER FOR FUTURE 5G MOBILE NETWORKS - ABDEL MOTAGALY, ZIAD (2017)
In this dissertation presents the design and simulation of a (K-band) E-plane waveguide bandpass filter for future 5G mobile networks. The mathematical derivation has been developed using Maple software and the 3D model of the filters is designed using the ANSYS High Frequency Structure Simulator (HFSS) software. With the given specification, the filter of the fifth order is required. The desired filter response is synthesized using Chebyshev polynomial. The S-parameter simulation results in HFSS shows that the centre frequency of the filter is 26 GHz with the bandwidth of 1 GHz is achieved. The mid-band return loss of the filter is more than 10 dB whereas mid-band insertion loss is less than 1 dB as desired. The stopband rejections are more than 30 dB 24.5 GHz and 27.5 GHz. With this performance, the project objectives are achieved and it is ready to be exported in IGES file for the CNC fabrication where the launchers can be added to the input and output before the testing and measurement using network analyser. Due to the time and budget constraints, the fabrication and measurement are to be carried out in the future work. This waveguide filter can potentially be used in base station of the 5 G network where the power handling capability and low loss performance is of prime importance.